Material handling cost optimization for a pushbelt manufacturing company using computerized relationship layout planning Algorithm - Dao, Le Duc; Hanh, Le Duc; Khoi, Truong Quoc (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
The strategic arrangement of a shop floor plays a crucial role in determining the operational effectiveness and financial performance of a manufacturing facility. The layout directly influences productivity, workflow, and even employee safety, making it a key factor in a plant's success. In this study, the objective is to refine the facility layout of a push belt manufacturing plant to decrease potential contract penalty fees that may arise from delays and to diminish the expenses associated with material handling. To address this challenge, the research adopts the computerized relationship layout planning (CORELAP) Algorithm to formulate an optimized layout. The implementation of this algorithm aims to reorganizing the shop floor to streamline the movement of workers and materials. The anticipated outcome of the newly designed layout is a significant reduction in the travel distance required for employees to complete their tasks. This optimization is expected to contribute to notable improvements in operation times and cost savings. Particularly, this enhancement results in the elimination of undesirable contract penalty fees and a notable reduction in material handling costs.